Exploring a potential mycoherbicidal agent for eco-friendly management of Trianthema portulacastrum L. - Saitheja, V; Thirukumaran, K; Sendhilvel, V; Karthikeyan, R; Kalarani, M K; Vellaikumar, S; Navarasu, S; Nagarajan, K (Plant Science Today, 2025)
Trianthema portulacastrum L. is one of the dominant weed species of the garden land ecosystem and poses a severe threat to crop cultivation. Chemical herbicides have the potential to manage the weed effectively, but their persistent residual nature negatively impacts the soil health and ecosystem. Therefore, biological approaches are being necessitated for weed management. Naturally, T. portulacastrum is highly susceptible to various fungal infections, resulting in severe defoliation and necrosis. Hence, a roving field survey was conducted at multiple locations in Tamil Nadu to collect the diseased T. portulacastrum samples and investigate the diversity of fungal pathogens associated with it. A total of 78 fungal isolates were isolated from the infected samples. A detached leaf assay was performed to screen the potential fungal isolates. Morpho-molecular analyses confirmed the potential isolates as Gibbago trianthemae and Fusarium spp. A polymorphism percentage of 68.88 % was observed among the potential G. trianthemae isolates, which were assessed using 10 different ISSR primers. Pot culture experiments revealed that G. trianthemae isolate TVM 2 recorded the maximum disease index of 34.4 %, 41.6 % and 49.3 % at 10, 20 and 30 DAI (days after inoculation), respectively, followed by isolate MDU 5. The potential fungal pathogen G. trianthemae also exhibited positive results for qualitative analysis of various extracellular and cell wall-degrading enzymes. Hence, there is a potential opportunity to exploit the infectious propagules of G. trianthemae for the development of a mycoherbicide formulation for environmentally friendly management of T. portulacastrum.